Immunity and behaviourof lambs born from ewes fed a flushing diet containing EPA and DHA - Nurlatifah, Aeni; Khotijah, Lilis; Arifiantini, Raden Iis; Maidin, Mashitah Sikh; Astuti, Dewi Apri; Herdis, Herdis (Indonesian Center for Animal Research and Development (ICARD), 2023)
Nutrition can influence lamb survival and the immune status during the neonatal phase until weaning.  This study aimed to investigate the effect of flushing of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) from Lemuru fish oil in the Ewe's diet on lamb immunity and survival.  Twenty-eight neonatal lambs were divided into four treatments according to Ewe's diet.  Four treatments: control concentrate (P1), flushing concentrate with  6% palm oil (P2), flushing concentrate with 3% lemuru oil and 3% palm oil (P3), and flushing concentrate with 6% lemuru oil (P4).  The Ewe were fed Napier grass and concentrated in a 30:70% ratio based on dry matter.  Ewe and their lambs remained together until weaning at about two months of age.  The parameter observed in ewes was colostrum Immunoglobulin G (IgG).  The parameters in the Lamb are blood Ig G, neonatal behavior of the Lamb, physiological response, and hematology of the Lamb at birth and weaning.  The results showed that feeding P4, P3, and P2 to the Ewe resulted in a shorter latency to stand-in lamb (P0.05).  P1 has higher leukocytes (P0.05) during weaning than P2 and P3.  P1 has the same leukocyte as P4.  Treatment has a non-significant effect (P0.05) on Ig G and physiological response.  In conclusion, administering 6% Lemuru oil containing EPA and DHA twice can shorten the latency to stand in newborn lambs.